(untitled) (Biological Sciences - PJSIR, 2003)
After establishing proper analytical methodology for multiple pesticide residues, cotton-growing areas of Multan Divi sion of Pakistan were surveyed and 40 samples of human mi lk from cotton pickers were collected during two crop seasons. Screening of these samples showed 72.5% contamination with 19 different pesticides/metabolites. The most frequently occurring pesticides were DDT and its metabolites, dimethoate, cyhalothrin, monocrotophos, profenofos and quinalphos.